Induced Burkholderia prophages detected from the hemoculture: a biomarker for Burkholderia pseudomallei infection - Withatanung, Patoo; Janesomboon, Sujintana; Vanaporn, Muthita; Muangsombut, Veerachat; Charoensudjai, Sorujsiri; Baker, Dave J.; Wuthiekanun, Vanaporn; Galyov, Edouard E.; Clokie, Martha R. J.; Gundogdu, Ozan; Korbsrisate, Sunee (Frontiers in Microbiology, 2024)
Bacteriophages (phages), viruses that infect bacteria, are found in abundance not only in the environment but also in the human body. The use of phages for the diagnostic of melioidosis, a tropical infectious disease caused by Burkholderia pseudomallei, is emerging as a promising novel approach, but our understanding of conditions under which Burkholderia prophages can be induced remains limited. Here, we first demonstrated the isolation of Burkholderia phages from the hemocultures of melioidosis patients. The B. pseudomallei-positive hemoculture bottles were filtered to remove bacteria and then phages were isolated and purified by spot and double agar overlay plaque assays. Forty blood samples (hemoculture-confirmed melioidosis) were tested, and phages found in 30% of samples. Transmission electron microscopy and genome analysis of the isolated phages, vB_HM387 and vB_HM795, showed that both phages are Myoviruses. These two phages were stable at a pH of 5-7 and temperatures of 25-37°C suggesting their ability to survive in human blood. The genome sizes of vB_HM387 and vB_HM795 are 36.3 and 44.0 kb, respectively. A phylogenetic analysis indicated that vB_HM387 has homologues but vB_HM795 is a novel Myovirus suggesting the heterogeneity of Burkholderia phages in melioidosis patients. The key finding that Burkholderia phages could be isolated from blood of melioidosis patients highlights the potential application of phage-based assay by detecting phages in blood as a pathogen-derived biomarker of infection.